OPERATIONAL PSYCHOLOGY - Trofimovs, Igors (Administrative and Criminal Justice, 2017)
The author deals with the history of formation of operational psychology as a field of knowledge influencing the national security. The author discloses in details some psychological essentials of the application of this knowledge in everyday activities of employees of special forces units, police, prosecutor’s office, courts, punishment execution system and other law enforcement institutions. The author also notes as important that during operational activities, in the process of determination of the truth, officers have not only to help in the reproduction of the facts, but also to try to achieve the truthfulness of the evidence. Because of applying, psychological techniques of operational investigative psychology create conditions for acquisition of correct and complete information about facts, particular events being of interest to law enforcement institutions ensuring necessary impact on persons who intentionally want to hide the truth and often forward false information. Therefore, the acquisition of psychological knowledge in the operational and investigative activities is a necessity for law enforcement institutions.